CNC Laser Cutting Machine - Jecha, Jiří (Univerzita Pardubice, 2019)
The goal of this thesis is to develop a complete software solution for a CNC laser cutting machine. Historical development of CNC technology and basic distinction of machining technologies are introduced. Software development starts with an overview of development tools and continues with a description of a created program division and methodology of writing the program. The machine's primary functions are described with an approach to creating a workable solution to presented problematics. CNC commissioning, with actuators (servomotors) tuning and minimising positional errors, is the major part of this thesis. Created a software solution and its functionalities are described in its visualisation environment. A test workpiece creation procedure is described.
CNC laserový řezací stroj
Keywords: CNC; laser; obrábění; řezání; servomotory; ladění; CNC; laser; machining; cutting; servomotors; tuning